JIYRENShENIŃ ShEShENLIK SÓZLERINIŃ IDEYALÍQ HÁM KÓRKEM-ESTETIKALÍQ ÓZGEShELIKLERI - Berdimuratov, J.A. (SCIENCE and SOCIETY, 2025)
The article typologically analyzes artistic features of proverbs and sayings of Karakalpak folklore. The closeness, similarity and unique characteristics of such words were scientifically analyzed.